A nation forged by crisis a new American history - Sexton, Jay 1978- (Basic Books, 2018)
"In A Nation Forged by Crisis, historian Jay Sexton contends that our national narrative is not one of halting yet inevitable progress, but of repeated disruptions brought about by shifts in the international system. Sexton shows that the American Revolution was a consequence of the increasing integration of the British and American economies; that a necessary precondition for the Civil War was the absence, for the first time in decades, of foreign threats; and that we cannot understand the New Deal without examining the role of European immigrants and their offspring in transforming the Democratic Party. A necessary corrective to conventional narratives of American history, A Nation Forged by Crisis argues that we can only prepare for our unpredictable future by first acknowledging the contingencies of our collective past"...